6. THE EFFECTIVENESS OF IMMIGRATION SUPERVISIONIN DETECTING MARRIAGESOF CONVENIENCE AS A MODE OF RESIDENCE PERMIT VIOLATION - Yasmin Iftina Rachmi; Koesmoyo Ponco Aji; Sohirin; Nur Priyanto; Suroso; Anwar Hendro; Tutidikatama; Yenni Astuti (Jurnal TNI Angkatan Udara, 2026)
This study aims to analyze the effectiveness of immigration supervision in detecting marriages of convenience as a form of residence permit violation. The study employs aqualitative approach using a literature review of 15 scientific articles discussing sham marriages,foreign national supervision, residence permit abuse, immigration law enforcement, and interagency coordination. The data were analyzed through content and thematic analysis involvingidentification, reduction, coding, thematic classification, comparison of findings, and conclusiondrawing. The results show that immigration supervision is conducted through administrativeexamination and field supervision. Early detection may be carried out by assessing documentvalidity, consistency of the spouses’ statements, relationship history, age differences, familybackgrounds, cohabitation, and the purpose of marriage. The effectiveness of supervisionremains constrained by difficulties in proving the parties’ intentions, limited human resources,broad supervisory areas, weak coordination, low public participation, and the absence ofstandardized examination indicators. Supervision can be strengthened through layeredverification, in-depth interviews, inter-agency data exchange, reinforcement of the ForeignersMonitoring Team, and post-permit monitoring. The study concludes that immigration supervisionplays an important role in preventing the misuse of marriage as a means of obtaining residencepermits, but its implementation must be strengthened to become more systematic, measurable,and sustainable.